Early Outcome of Hypoxic Ischemic Encephalopathy in Neonates Born at Nazeer Hussain Medical Complex Hyderabad (Medical Forum Monthly, 2024)
Objective: To assess the early outcome of Hypoxic Ischemic Encephalopathy in neonates born at Nazeer Hussain Medical Complex HyderabadStudy Design: Descriptive / cross sectional studyPlace and Duration of Study: This study was conducted at the Neonatal Ward of Nazeer Hussain Medical Complex, Hyderabad from January to December 2016.Materials and Methods: This study was conducted to know the early outcome of birth asphyxia in neonates born at this hospital. Inclusion criteria of our study were all newborn ( term, preterm or post-term) with history of perinatal asphyxia or APGAR score at 5 minutes, < 7, or delayed crying after birth or > 10 minutes resuscitation soon after birth. Neonates having lethal anomalies like hydrops fetalis, cyanotic heart defects and congenital malformations were excluded from study. Severity of Asphyxia was assessed by the grading of Hypoxic Ischemic Encephalopathy. APGAR score 5-7 was labeled as mild asphyxia, 3-5 as moderate asphyxia and <3 as severe Asphyxia.Results. In this study mostly male neonates were there 92.2% (Table 1). Most common of admission was ≤ 2 days 51.2% (Table 1). Most of the neonates were ≥ 37 weeks gestational age 48.8% (Table 1). Grade 1 Hypoxic Ischemic Encephalopathy was most common 41.5% (Table 2). Most of the mothers had age between 25 to 35 years 90.2% (Table 2). Most mothers had the history of multigravida 53.7% (Table 2). Most common fetal presentation was cephalic 80.5% (Table 2). 56.1% neonates born by C-section (Table 2). Only 7.3% mothers had history of prolonged labor (Table 2). 33% neonates died due to Hypoxic Ischemic Encephalopathy (Table 3).Conclusion: In this study most common type was grade 1 Hypoxic Ischemic Encephalopathy 37.1%. Grade 3 HIE was least common but death rate was more in it 21.9%. Death was least common in grade 1 HIE 4.26%.